Prevalence of iron deficiency anaemia among children under the age of 5 years in paediatric hospitals- Benghazi, Libya - kamal, mona (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Iron deficiency anaemia is the most common form of anaemia. This study was undertaken to highlight the prevalence of iron deficiency anaemia among children aged less than 5 years. A total of 220 children aged less than 5 years - attended at the haematology laboratory of Children Hospital, Benghazi Libya - were enrolled in the study. The prevalence of iron deficiency anaemia was estimated. Our study showed that 109  (49.5%) of all children were anaemic and of them, 57 children (52.3 %) were moderately anaemic. This work concluded that there is a high prevalence of anaemia among Libyan children under the age of 5 years.